ECONOMETRIC DYNAMIC INVESTMENT MODEL ON THE EXAMPLE OF THE DATA OF THE REPUBLIC OF KAZAKHSTAN - Babich В. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article examines the analysis of one of the most significant macroeconomic categories that affect the country’s economic growth - gross investment. The author, on the basis of statistical information for the period 1993-2020, determines the dependence of current investments on investments of the previous period and the growth rate of real gross domestic product. An autoregressive dynamic model is considered. A regression equation is constructed that gives estimates of the nonlinear investment function. For the construction, the author uses the method of partial correction, which eliminates such a problem as the bias of the estimates obtained. Key words: economic model, macroeconomics, economic growth, investment, autoregressive dynamic model, multicollinearity, analysis of variance, hypothesis testing.